Costul vieții în rural - Mihăilescu, Adina (Calitatea Vieții, 2013)
The article gives us a true picture of the purchasing power of goods and services from the market. The incomes of many types of customers, such as: persons, families, households are a good indicator to measure the cost of living in rural areas. The Research Institute for the Quality of Life uses to measure the poverty the normative method, which is based on consumption. The quantity and quality of products are established by the specialized studies, and do not depend on the consumption levels recorded in time, but on the development and every day manifestation of persons in their family or outside. We calculated two consumer baskets: the consumer basket related to the decent minimum standardofliving, and the subsistence level consumer basket. The differences between the decent and the subsistence level consumer basket derive from the fact that it is necessary to subtract some expenditures in determining this subsistence level, like: expenditures for cultural services, mail and telecommunications, etc.). We monitored the different types of families in rural areas: active persons working in agriculture, and, also, the pensioners. We used equivalence scales, in order to calculate the expenditure per household member. The consumer basket is a tool to measure the level of poverty of the people from rural areas. The development of rural services is an opportunity to create jobs and, also, a condition which allows increasing the income of the rural population. The cost of living for the rural households with one or more members was far below the cost of living of the urban households with similar structure. Many rural households have resources below the minimum requirement for a decent living standard, as well as below the minimum subsistence standard established by the normative method.